2017
DOI: 10.1515/taa-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities via s−convexity and log −convexity

Abstract: Abstract:In this paper, we obtain some new inequalities for functions whose second derivatives' absolute value is s−convex and log −convex. Also, we give some applications for numerical integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We begin the section by recalling the important Fejér inequality (see [3]) and the famous Hermite-Hadamard inequality (see [4,5] 1) and the substitution h(x) = 1 yields the Hermite-Hadamard inequality:…”
Section: Applications and Generalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin the section by recalling the important Fejér inequality (see [3]) and the famous Hermite-Hadamard inequality (see [4,5] 1) and the substitution h(x) = 1 yields the Hermite-Hadamard inequality:…”
Section: Applications and Generalizationsmentioning
confidence: 99%
“…Inequalities for m-convex functions on the bounded interval of nonnegative real numbers were considered in [2]. Research on inequalities via s-convexity and log -convexity can be found in [1]. Usage of functionals in studying inequalities can be seen in [13].…”
Section: Corollary 32 Let I ⊆ R Be An Interval Containing the Zero And Let ∑ N I=1 T I X I Be A Convex Combination Of Points X I ∈ I Withmentioning
confidence: 99%